P802 Perforating Crohn's Disease and pancolitis as risk factors for incident cancer: a prospective multi-centre nested case–control IG-IBD study at 6 years. (25th January 2019) - Petruzziello, C; Armuzzi, A; Scribano, M L; Castiglione, F; D'incà, R; Daperno, M; Papi, C; Vecchi, M; Fries, W; Riegler, G; Alvisi, P; Mocciaro, F; et al.
Abstract: Background: In a prospective, multi-centre, nested case–control study at 6 years (years), we aimed to characterise incident cases of cancer in inflammatory bowel disease (IBD). Secondary end point was to evaluate risk factors for cancerc in IBD. Methods: From 31 December 2011 to 31 December 2017, all incident cases of cancer in IBD patients referring to 16 IG-IBD Units (≥2 visits/year) were recorded. Each IBD patient with incident cancer was matched with 2 IBD patients with no cancer for: IBD type (Crohn's disease, CD; ulcerative colitis, UC), gender, age (±5 years). Data expressed as median (range). Wilcoxon, χ 2, Fisher exact test, multi-variate logistic regression analysis (OR [95% CI]). Results: Incident cancer occurred in 403 IBD patients: 204 CD (CD-K), 199 UC (UC-K). Overall, 1209 IBD patients were considered (403 IBD-K; 806 IBD-C). In IBD, cancer ( n = 403) involved ( n = [%]): digestive system (129 [32%]), skin (60 [14.9%]: 27 NMSC, 31 melanoma, 2 others), urinary tract (39 [9.7%]), lung (28 [6.9%]), breast (22 [5.5%]), genital tract (26 [6.5%]), thyroid (8 [1.98%]), lymphoma (11 [2.72%] all in CD), small bowel cancers (16 [3.9%];15 CD [7.3%], 1 UC ileal pouch [0.5%]), others (64[15.9%]). Cancer frequency was comparable between CD and UC considering ( n = [%]):digestive system (61[30%] vs. 6 [34%]);skin (33[16%] vs. 27[13.5%]);lung (14[6.8%] vs. 14 [7.0%]);breast (22[10.7%] vs. 24[12.1%]);genital tract (15[7.3%] vs. 11 [5.5%];p>0.05). Colorectal and urinary tract cancers were more frequent in UC vs. CD (58[29%] vs. 35[17%], p < 0.005;26[13%] vs. 13[6.3%], p = 0.039). Extracolonic cancers were more frequent in CD vs. UC (35/204 [17%] vs. 58/199 [29%]; p < 0.005). Risk factors considered: age (<40 vs. ≥40 years), IBD duration (< 10 vs. ≥10 years), smoking (Yes/No), ISS and/or anti-TNFα (Y/N), IBD-related surgery, UC extent, CD pattern, perianal CD risk factors for any cancer identified in UC: UC-related surgery (4.63 [2.62–8.42]), extensive vs. distal UC (1.73 [1.10–2.75]). The other risk factors were not significant (OR 1.30 [0.74–2.39]; 0.92 [0.63–1.35]; 0.92 [0.55–1.52]; 0.84 [0.51–1.38]; 1.54 [0.95–2.51], respectively). In CD, perforating pattern was the only significant risk factor (OR 2.33 [1.33–4.11]) (other risk factors: OR 0.93 [0.59–1.48]; 0.98 [0.67–1.43]; 0.74 [0.51–1.07]; 1.31 [0.90–1.92]; 0.97 [0.62–1.51]; 1.25 [0.79–2.01]; 1.02 [0.65–1.60]).In CD, the frequency of B3 pattern was higher in CD-K vs. CD-C (26% [54/204] vs. 15% [63/408]; p = 0.0033).The frequency of extensive UC was higher in UC-K vs. UC-C (51% [101/199] vs. 38% [152/398]; p = 0.0045). Conclusions: In a prospective, multi-centre, nested-case–control study at 6 years, penetrating CD, extensive UC and UC-related surgery were significant risk factors for any incident cancer. Clinical characteristics of severity of IBD may increase the overall cancer risk. Lymphoma and SBC were associated with CD.